Is gender diversity the next frontier on boardroom in the construction industry? - Azra, Tilai; Josephine Yau, Tan Hwang; Audrey Kho, Jia En; Audrey, Liwan; Jerome, Kueh (UiTM Press, 2024)
The paradigm that posits women as unsuitable corporate leaders has become a heated topic for debates prompting boardroom gender diversity to be a popular corporate governance issue. Based on the business case for gender diversity, this study examines the effect of boardroom gender diversity from an industry-specific perspective, particularly in the construction industry in Malaysia. The study follows a quantitative research method and uses panel data from 80 listed construction firms for the period between 2010 and 2019. To obtain a comprehensive measure, gender diversity is proxied by the proportion of female directors on the board, Blau's Index, female CEO, female CFO, female directors' education, and previous experience. Contrary to several past research, the results show no significant effect from gender diversity proxies on firm performance measured by Tobin's Q, while only female CEO has a significantly negative effect on ROA. Thus, the current study found no evidence to posit a business case for board gender diversity in the context of the Malaysian construction industry. The results may not reflect the true picture considering the small sample size employed or the cultural resistance and tokenism issue that still exists in society. The research findings extend the literature on emerging economies and have important implications for the industry, policymakers, and society.